1997
DOI: 10.1161/01.atv.17.8.1527
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin: An Effective Lipid-Modifying Agent in Familial Hypercholesterolemia

Abstract: Hydroxymethylglutaryl coenzyme A (HMG-CoA) reductase inhibitors are the drugs of choice in heterozygous familial hypercholesterolemia (FH), which has a high risk of ischemic heart disease. An open-label study was conducted to test the efficacy and safety of atorvastatin, a new synthetic HMG-CoA reductase inhibitor in proven FH. After a 4-week placebo phase, 22 subjects were randomized to either 80 mg atorvastatin at night (n = 11) or 40 mg twice a day for 6 weeks. The two dosage groups were well matched and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 24 publications
3
29
1
1
Order By: Relevance
“…21) In addition, Marais et al administered ATV (80 mg/d) for 6 weeks to 22 patients with familial hypercholesterolemia, and reported that SUA levels decreased by approximately 10% from 4.87 to 4.36 mg/dL. 22) The SUA-lowering effect of ATV in these patients is the result of a dose that far exceeds the maximum daily dose of 20 mg allowed in Japan. In this study, we could demonstrate the SUA-lowering effect of ATV at the average dose of 8.8 mg/d, which is less than the dose reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…21) In addition, Marais et al administered ATV (80 mg/d) for 6 weeks to 22 patients with familial hypercholesterolemia, and reported that SUA levels decreased by approximately 10% from 4.87 to 4.36 mg/dL. 22) The SUA-lowering effect of ATV in these patients is the result of a dose that far exceeds the maximum daily dose of 20 mg allowed in Japan. In this study, we could demonstrate the SUA-lowering effect of ATV at the average dose of 8.8 mg/d, which is less than the dose reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Several large clinical trials examining lipoprotein and apolipoprotein responses with atorvastatin have shown HDL cholesterol and apoA-I increases of 3% to 8% at lower doses of atorvastatin (10 to 20 mg), 3,7,8,13 whereas at higher doses (40 to 80 mg atorvastatin), levels of HDL cholesterol and apoA-I are generally either minimally elevated or not significantly different from placebo. 3,7,8,20 In general, the rise in apoA-I, the major protein component of HDL, tends to be smaller than that of HDL cholesterol. 7,8,13,20 For example, in comparative human trials of simvastatin and atorvastatin therapies, both the apoA-I and HDL cholesterol percentage increases tended to be lower with high-dose atorvastatin versus simvastatin regimens but were significantly lower only for the apoA-I response.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,8,20 In general, the rise in apoA-I, the major protein component of HDL, tends to be smaller than that of HDL cholesterol. 7,8,13,20 For example, in comparative human trials of simvastatin and atorvastatin therapies, both the apoA-I and HDL cholesterol percentage increases tended to be lower with high-dose atorvastatin versus simvastatin regimens but were significantly lower only for the apoA-I response. 7,8 As observed in humans, in the rabbits in the present study, the apoA-I response to high-dose atorvastatin was more negative than the HDL cholesterol response 3 weeks after treatment (Ϫ4.2% change in HDL cholesterol and Ϫ19.4% change in apoA-I).…”
Section: Discussionmentioning
confidence: 99%
“…The drugs in use include pitavastatin, rosuvastatin, atorvastatin, simvastatin, fluvastatin, pravastatin, and lovastatin. There is considerable variation in the statin lowering response of LDL cholesterol (À25 to 60%) [45,46]. Genetic determinants of responsiveness to the statins cannot be excluded [47].…”
Section: Lipid-lowering Drugsmentioning
confidence: 99%